2017
DOI: 10.1016/j.reprotox.2016.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Vertebrate embryos as tools for anti-angiogenic drug screening and function

Abstract: The development of new angiogenic inhibitors highlights a need for robust screening assays that adequately capture the complexity of vessel formation, and allow for the quantitative evaluation of the teratogenicity of new anti-angiogenic agents. This review discusses the use of screening assays in vertebrate embryos, specifically focusing upon chicken and zebrafish embryos, for the detection of anti-angiogenic agents.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
6
1

Relationship

5
2

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 159 publications
(186 reference statements)
0
12
0
Order By: Relevance
“…Indeed, he described how the drug's actions on blood vessels can result in a range of limb damage (Vargesson, , ; Vargesson and Hootnick, ). He also described the advances his team has made in finding a “safe” form of the drug, retaining the clinical benefits but without the side‐effect of embryonic damage (Beedie et al, ). This is extremely relevant today as sadly new generations of thalidomide children have been born in recent decades in Brazil as the original drug is used to treat a form of Leprosy (Schuler‐Faccini et al, ; Vianna et al, ; Vargesson, ).…”
Section: Legacy Of Thalidomide Meetingmentioning
confidence: 99%
“…Indeed, he described how the drug's actions on blood vessels can result in a range of limb damage (Vargesson, , ; Vargesson and Hootnick, ). He also described the advances his team has made in finding a “safe” form of the drug, retaining the clinical benefits but without the side‐effect of embryonic damage (Beedie et al, ). This is extremely relevant today as sadly new generations of thalidomide children have been born in recent decades in Brazil as the original drug is used to treat a form of Leprosy (Schuler‐Faccini et al, ; Vianna et al, ; Vargesson, ).…”
Section: Legacy Of Thalidomide Meetingmentioning
confidence: 99%
“…Previously we have shown that drugs such as thalidomide and some of its analogs 35 , 37 39 as well as antiangiogenic agents such as Sunitinib 29 , 34 cause damage to a range of tissues including the fins, otic vesicle and eyes through disrupting blood vessel formation. To investigate if blood vessel loss or patterning defects occur in zebrafish embryos following NA/EE-mixture exposure we used the transgenic fli1 :EGFP reporter line of zebrafish embryos 40 .…”
Section: Resultsmentioning
confidence: 99%
“…The zebrafish embryo has become increasingly popular in drug screening assays due to its rapid development, optical transparency and the ability to visualise and follow development live and in vivo 29 . Indeed, many drugs have actions in zebrafish embryos that are similar to actions in mammalian species including humans.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…We also know that thalidomide survivors themselves exhibit a wide range of cardiovascular changes, including heart defects, some of which might actually contribute to the differences seen in thalidomide survivors (Tajima et al, 2016; see also Vargesson and Hootnick, 2017). In further support of this mechanism, multiple anti-angiogenic drugs used as anti-cancer agents, for example sunitinib and sorafenib (Beedie et al, 2016a), which induce cell death, have a wide range of molecular targets and all of these can cause limb damage (Beedie et al, 2016a(Beedie et al, , 2017. This indicates that vessel inhibition is a key element underlying druginduced limb defects.…”
Section: Anti-angiogenesis Modelmentioning
confidence: 99%